2010
DOI: 10.1111/j.1750-3841.2010.01541.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory Effects of Limonene from Yuzu (Citrus junos Tanaka) Essential Oil on Eosinophils

Abstract: Yuzu (Citrus junos Tanaka) has been used as a traditional medicine in Japan. We investigated in vitro anti-inflammatory effects of limonene from yuzu peel on human eosinophilic leukemia HL-60 clone 15 cells. To examine anti-inflammatory effects of limonene on the cells, we measured the level of reactive oxygen species (ROS), monocyte chemoattractant protein-1 (MCP-1), nuclear factor (NF) kappa B, and p38 mitogen-activated protein kinase (MAPK). We found that low concentration of limonene (7.34 mmol/L) inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 49 publications
2
97
2
1
Order By: Relevance
“…The use of a mixture of long-chain inulin and oligosaccharide in HLA-B27 transgenic rats exhibited some local anti-inflammatory properties, through the reduction of gross cecal and inflammatory histological scores in the cecum and colon, the decreased levels of the pro-inflammatory cytokine IL-1β, and the increased of the anti-inflammatory TGF-β (Hoentjen et al, 2005). The results of Hirota et al (2010) suggest that low concentrations of limonene from Yuzu, a traditional medicine used in Japan have anti-inflammatory effect by inhibiting cytokines, ROS production, and inactivating eosinophil migration. Limonene and beta-myrcene from essential oils of two species of Asteraceae produced also significantly less IFN-γ and IL-4 and inhibited cell migration when administered orally in a mouse model of pleurisy induced by zymosan and lipopolysaccharide (LPS) (Souza et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The use of a mixture of long-chain inulin and oligosaccharide in HLA-B27 transgenic rats exhibited some local anti-inflammatory properties, through the reduction of gross cecal and inflammatory histological scores in the cecum and colon, the decreased levels of the pro-inflammatory cytokine IL-1β, and the increased of the anti-inflammatory TGF-β (Hoentjen et al, 2005). The results of Hirota et al (2010) suggest that low concentrations of limonene from Yuzu, a traditional medicine used in Japan have anti-inflammatory effect by inhibiting cytokines, ROS production, and inactivating eosinophil migration. Limonene and beta-myrcene from essential oils of two species of Asteraceae produced also significantly less IFN-γ and IL-4 and inhibited cell migration when administered orally in a mouse model of pleurisy induced by zymosan and lipopolysaccharide (LPS) (Souza et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…5,6) For example, anti-in ammatory and anti-cancer e ects of essential oils containing geraniol or limonene have been reported. [7][8][9] More interestingly, it has been reported that exposure of rat brain tissues to citrus avor components results in the release of dopamines. 10) e concentrations of MTs in air in a forest are below 1 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese also use yuzu to make various sweets, including marmalade, jellies, and cakes. According to food and nutritional science studies, yuzu also possesses antioxidant, 2 anticarcinogenic, 3 anti-inflammatory, 4 and antidiabetic properties 5 and exhibits preventive effects on cognitive dysfunction. 6 The pale yellow essential oil extracted from yuzu rind by the cold expression method emits an exquisite citrus aroma.…”
Section: Introductionmentioning
confidence: 99%